Long-Term Administration of Dehydroepiandrosterone Accelerates Glucose Catabolism via Activation of PI3K/Akt-PFK-2 Signaling Pathway in Rats Fed a High-Fat Diet - Kang, Jian (Public Library of Science, 2016)
Dehydroepiandrosterone (DHEA) has a fat-reducing effect, while little information is available on whether DHEA regulates glucose metabolism, which would in turn affect fat deposition. To investigate the effects of DHEA on glucose metabolism, rats were administered a high-fat diet containing either 0 (HCG), 25 (HLG), 50 (HMG), or 100 (HHG) mg·kg-1 DHEA per day via gavage for 8 weeks. Results showed that long-term administration of DHEA inhibited body weight gain in rats on a high-fat diet. No statistical differences in serum glucose levels were observed, whereas hepatic glycogen content in HMG and HHG groups and muscle glycogen content in HLG and HMG groups were higher than those in HCG group. Glucokinase, malate dehydrogenase and phosphofructokinase-2 activities in HMG and HHG groups, pyruvate kinase and succinate dehydrogenase activities in HMG group, and pyruvate dehydrogenase activity in all DHEA treatment groups were increased compared with those in HCG group. Phosphoenolpyruvate carboxykinase and glycogen phosphorylase mRNA levels were decreased in HMG and HHG groups, whereas glycogen synthase-2 mRNA level was increased in HMG group compared with those in HCG. The abundance of Glut2 mRNA in HMG and HHG groups and Glut4 mRNA in HMG group was higher than that in HCG group. DHEA treatment increased serum leptin content in HMG and HHG groups compared with that in HCG group. Serum insulin content and insulin receptor mRNA level in HMG group and insulin receptor substrate-2 mRNA level in HMG and HHG group were increased compared with those in HCG group. Furthermore, Pi3k mRNA level in HMG and Akt mRNA level in HMG and HHG groups were significantly increased than those in HCG group. These data showed that DHEA treatment could enhance glycogen storage and accelerate glucose catabolism in rats fed a high-fat diet, and this effect may be associated with the activation of PI3K/Akt-PFK-2 signaling pathway.